An innovative environmental risk assessment approach to a Mediterranean coastal forest: the Presidential Estate of Castelporziano (Rome) case study - Recanatesi, Fabio; Giuliani, Chiara; Piccinno, Matteo; Cucca, Benedetta; Rossi, Carlo Maria; Ripa, Maria Nicolina (Annals of Silvicultural Research, 2020)
Thanks to their ability to generate ecosystem services, forest ecosystems have a significant social, economic and environmental impact on the development of many regions in the world, especially those located in urban and peri-urban areas. Today, increased forest vulnerability is reflected in an increased number of episodes of severe decline associated mainly with drought. In this context, the Mediterranean area shows high forest vulnerability and a subsequent decline in its natural renewal rate. In this scenario, the aim of this research is to assess the sustainability of a protected pristine deciduous oak forest near Rome via the development of a forest health condition monitoring tool based on the application of multispectral satellite data and the identification of silvicultural models suitable to promoting natural forest renewal. Data and results from research in the case study area, the Natural State Reserve of Castelporziano (Rome), have potential as an important decision making tool in sustainable forest management.